Pelatihan Terapi Pijat Bayi Bagi Ibu Dengan Balita Di Desa Kualu Kecamatan Tambang - Eva Santi Hutasoit; Linda Suryani; Yessi Azwar; Siska Mulyani; Tengku Hartian; Rika Sri Wahyuni (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
The purpose of this community service activity is to provide understanding to mothers with toddlers about the implementation of infant massage therapy. Apart from having good benefits for the baby, this therapy is also a solution for ARI and bloating in babies. The implementation of this activity uses consultation, practice, and evaluation methods with four stages of activity. Based on the implementation of the activities, it was found that after receiving infant massage therapy training, the mother's understanding of infant massage therapy would increase. This result is proven by the mother's pre-test knowledge test in the poor category as many as 9 people (53%), good category as many as 8 people (47%). And at the time of the post test the level of mother's knowledge was less than 1 person (6%) and good as many as 16 people (94%).